Voriconazole is inferior to amphotericin B deoxycholate as the initial induction therapy for HIV-associated Talaromyces marneffei fungemia: A multicenter retrospective study. - Shasha Ye; Jiaying Qin; Xingguo Miao; Guanjing Lang; Mengyan Wang; Gong Chen; Feifei Su; Lijun Xu (PLoS Neglected Tropical Diseases)
Background The optimal initial induction treatment for HIV-associated Talaromyces marneffei fungemia (HTMF) remains unclear. Methods Three hundred and fifteen patients with HIV-associated Talaromyces marneffei were enrolled in this multicenter retrospective study. The effectiveness of induction regimens with amphotericin B deoxycholate (iAmBd), voriconazole (iVori), and a switch regimen from iVori to AmBd (iVori→AmBd switch) on 180-day all-cause mortality in HTMF patients was assessed. Results The prevalence of HTMF was 75.9% (239/315) with a 180-day all-cause mortality of 20.1% (48/239). Among these HTMF patients, 44.4% (106/239) were treated with iAmBd, 41.8% (100/239) with iVori, and 13.8% (33/239) with other regimens. Additionally, 53% (53/100) of patients treated with iVori underwent an iVori→AmBd switch within 7 days. The 180-day cumulative survival rates were 88.7% for patients treated with iAmBd and 77.0% for those treated with iVori; 88.8% for patients who received AmBd within 3 days (iAmBd + 3-day iVori→AmBd switch) and 72.2% for those who continued iVori; 88.2% for patients who received AmBd within 5 days (iAmBd + 5-day iVori→AmBd switch) and 71.0% for those who continued iVori; 88.1% for those who received AmBd within 7 days (iAmBd + 7-day iVori→AmBd switch) and 66.0% for those who continued iVori (all log-rank P < 0.020). The prevalence of adverse drug reactions (ADRs) was 24.5% in the iAmBd group and 9.0% in the iVori group in induction stage (P < 0.001). Conclusion Voriconazole is inferior to AmBd as an initial induction therapy for HTMF patients. Early AmBd administration or an early iVori→AmBd switch improves survival, despite the higher incidence of AmBd-related ADRs.